Personality Dimensions in Young people with Anxiety Disorders - Naumovska, Andromahi; Raleva, Marija; Bonevski, Dimitar; Isjanovski, Viktor (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
The personality is a product of biological determination that is shaped under the influence of the process of socialization. Early inhibitions of certain behaviors in children are factors to later development of inhibited or timid individual. These traits continue to develop through adolescence to adulthood and increase the risk for developing anxiety disorders. Aim: This study was created to make an assessment of personality dimensions in young individuals with anxiety disorders.